A new species of Etrocorema from Yunnan, China, with a redescription of the male of E. hochii (Wu, 1938) (Plecoptera: Perlidae) - Wang, Yingying; Wang, Guoquan; Li, Weihai (Zootaxa, 2024)
A new species of Etrocorema, E. wui sp. nov. is described from Yunnan Province, China as new to science and compared with related species. A supplementary description of the male of Etrocorema hochii (Wu, 1938) from Hainan Province, China is also given. A male neotype of E. hochii is designated for the species.